Radioactive fallouts as temporal makers for glacier ice cores dating - CLEMENZA, MASSIMILIANO; CUCCIATI, GIACOMO; MAGGI, VALTER; PATTAVINA, LUCA MARIA; Previtali, E. (The European Physical Journal Plus, 2012)
In this paper, we intend to show how analytical methods used in nuclear physics, as gamma spectroscopy, are powerful tools for the dating of environmental archives. Specifically, we will show how events related to the release in the environment of great amount of radioactive isotopes (e.g., atmospheric nuclear test explosions) can be used as temporal markers in alpine glaciers. The radio-isotope selected for the dating of ice carrots is Cs-137, because of its chemical and nuclear properties. The radioactive measurements have been conducted using a low-background high-purity germanium detector. The sensitivity for the prepared samples is 10 mBq/kg. We will illustrate how dating curves (date versus depth of the sample) can be considered as an absolute calibrator for all the other chemical dating methods used on glacier samples analyses